2019
DOI: 10.1103/physrevd.99.014022
|View full text |Cite
|
Sign up to set email alerts
|

Prediction for 5++ mesons

Abstract: In this paper, we study the spectrum and decay behavior of 5 ++ meson family which is still missing in experiment. By the modified Godfrey-Isgur model with a color screening effect, we obtain the mass spectrum of a 5 , f 5 and f ′ 5 mesons. And we predict their two-body strong decays by means of a phenomenology quark pair creation model. This study is crucial to establish J PC = 5 ++ meson family and it is also helpful to search for these states in the future.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 51 publications
3
33
0
3
Order By: Relevance
“…211The as-synthesized CNTs-Fe 3 O 4 nanohybrids are highly aggregated due to strong hydrophobic, localized vdW, and magnetic attractions, but 2 wt % carboxymethylcellulose can effectively disperse CNTs-Fe 3 O 4 particles by electrosteric repulsions. A novel transport feature was characterized by an initial lower effluent peak, followed by a sharp, higher effluent peak, probably due to the interplay between the variability of fluid viscosity (water and viscous carboxymethylcellulose) and size-selective retention (232) of CNTs-Fe 3 O 4 . The predicted maximum transport distance of CNTs-Fe 3 O 4 using the Tufenkji-Elimelech model(233) ranges between 0.38-46 m, supporting the feasibility of applying the magnetically recyclable CNTs-Fe 3 O 4 for in situ nanoremediation.…”
Section: Aggregation Of Cmnhsmentioning
confidence: 99%
“…211The as-synthesized CNTs-Fe 3 O 4 nanohybrids are highly aggregated due to strong hydrophobic, localized vdW, and magnetic attractions, but 2 wt % carboxymethylcellulose can effectively disperse CNTs-Fe 3 O 4 particles by electrosteric repulsions. A novel transport feature was characterized by an initial lower effluent peak, followed by a sharp, higher effluent peak, probably due to the interplay between the variability of fluid viscosity (water and viscous carboxymethylcellulose) and size-selective retention (232) of CNTs-Fe 3 O 4 . The predicted maximum transport distance of CNTs-Fe 3 O 4 using the Tufenkji-Elimelech model(233) ranges between 0.38-46 m, supporting the feasibility of applying the magnetically recyclable CNTs-Fe 3 O 4 for in situ nanoremediation.…”
Section: Aggregation Of Cmnhsmentioning
confidence: 99%
“…Recently Li and co-workers described novel luminescent soft materials via reaction of Eu 3+ -coordinated carboxyl functionalized ionic liquids with terpyridine functionalized imidazolium salts (Figure 22). These ligands are built from an imidazolium ring substituted on one side with a terpyridine derivative and, on the opposite side, a paraffin chain of various lengths [57].…”
Section: Carboxylatesmentioning
confidence: 99%
“…From the Review of Particle Physics, there exist four J P C = 1 −− observed states around 2.2 GeV, such as φ(2170), ρ(2150), ω(2205) and ρ(2270) [2]. The φ(2170) state with I G (J P C ) = 0 − (1 −− ), labeled previously as Y (2175), has been investigated within many theoretical interpretations, which include conventional ss state [3][4][5][6][7], hybrid state [3,8], tetraquark state [9][10][11][12][13][14], ΛΛ( 3 S 1 ) bound state or hexaquark state [15][16][17][18][19], and φKK resonance state [20,21]. The ρ(2150), ω(2205) and ρ(2270) are also studied as conventional radial or orbital excited mesons in the consistent quark model [22][23][24].…”
Section: Introductionmentioning
confidence: 99%